Experimental Study on the Influence of Lubrication Condition on Scuffing Damage of Gear Under Low Speed and Heavy Load - Chao Chen; Lubing Shi; Jiqiang Li; Zhongming Liu (Jixie chuandong)
In order to study the influence of lubrication conditions on the scuffing damage of gear under low speed and heavy load， the meshing of gear teeth is simulated by a pair of ring specimens in rolling and sliding contact， and the scuffing tests of 18CrNiMo7-6 carburized steel gear material under different lubrication conditions are carried out on MJP-30A rolling wear testing machine. The variation of friction coefficient among different tests and the surface morphology of the specimens after tests are analyzed. The results show that the contact stress of scuffing damage is 1 927 MPa under the dry friction condition， and the friction coefficient decreases with the increase of contact stress before scuffing damage occurs. Under the good lubrication， no scuffing occurs even when the contact stress is increased as high as 3 047 MPa， and the friction coefficient decreases with the increase of contact stress during the test. Under the condition of oil scarcity， the friction coefficient increases obviously with the increase of oil scarcity， and the scuffing damage occurs only when the friction coefficient almost increases to the level of dry friction coefficient. Therefore， in order to avoid the scuffing damage of the gear tooth surfaces in the operation under low speed and heavy load， the lubrication status should be taken as an important monitoring index of preventing the serious starvation of lubrication or dry friction contact from occurring in the meshing of tooth surfaces.